1990
DOI: 10.1126/science.250.4983.931
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Flower Development by Homeotic Genes in Antirrhinum majus

Abstract: Homeotic mutants have been useful for the study of animal development. Such mutants are also known in plants. The isolation and molecular analysis of several homeotic genes in Antirrhinum majus provide insights into the underlying molecular regulatory mechanisms of flower development. A model is presented of how the characteristic sequential pattern of developing organs, comprising the flower, is established in the process of morphogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
474
1
6

Year Published

1994
1994
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 813 publications
(485 citation statements)
references
References 25 publications
4
474
1
6
Order By: Relevance
“…This contrasts with recent progress in elucidation of control of development of other floral organs, where analysis offloral homeotic mutants in Arabidopsis thaliana and Antirrhinum majus has led to the formulation of two similar models for genetic determination of the identity of the four major floral organs (4)(5)(6)(7)(8). In Arabidopsis, at least five genes-APETALA1 (API), AP-ETALA2 (AP2), APETALA3 (AP3), PISTILLATA (PI), and AGAMOUS (AG)-are responsible for this determination (5,(8)(9)(10)(11).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…This contrasts with recent progress in elucidation of control of development of other floral organs, where analysis offloral homeotic mutants in Arabidopsis thaliana and Antirrhinum majus has led to the formulation of two similar models for genetic determination of the identity of the four major floral organs (4)(5)(6)(7)(8). In Arabidopsis, at least five genes-APETALA1 (API), AP-ETALA2 (AP2), APETALA3 (AP3), PISTILLATA (PI), and AGAMOUS (AG)-are responsible for this determination (5,(8)(9)(10)(11).…”
mentioning
confidence: 68%
“…Our observation that ovule integuments can be converted to a carpel by the loss of a single gene may have implications for theories on the evolutionary origins of integuments and carpels, a topic that remains controversial (1,2,32). In combination with ongoing research on the determination of major floral organs (4)(5)(6)(7)(8), further studies on bell and on additional mutations affecting ovule development will allow construction of increasingly predictive and accurate molecular-genetic models of flower and ovule ontogeny.…”
Section: Resultsmentioning
confidence: 99%
“…For example, developmental mutants of large and epistatic effect are sometimes observed by developmental biologists and have been elegantly used to clarify processes of floral development (e.g., Schwarz-Sommer et a!., 1991). Other within-species studies have revealed that single gene mutations are responsible for changes in timing and rates of development in nematodes (Ambros, 1988) and tomato floral characters (Sawhney, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Each MADS-box protein contains a DNAbinding domain, known as a MADS box, which consists of 57 strongly conserved amino acids (Schwarz-Sommer et al, 1990;Ma et al, 1991). MADS-box proteins play key roles as transcription factors.…”
Section: Introductionmentioning
confidence: 99%